Rice Cellulose SynthaseA8 Plant-Conserved Region Is a Coiled-Coil at the Catalytic Core Entrance - Rushton, Phillip S. (Plant Physiol, 2017)
The crystallographic structure of a rice (Oryza sativa) cellulose synthase, OsCesA8, plant-conserved region (P-CR), one of two unique domains in the catalytic domain of plant CesAs, was solved to 2.4 Å resolution. Two antiparallel α-helices form a coiled-coil domain linked by a large extended connector loop containing a conserved trio of aromatic residues. The P-CR structure was fit into a molecular envelope for the P-CR domain derived from small-angle X-ray scattering data. The P-CR structure and molecular envelope, combined with a homology-based chain trace of the CesA8 catalytic core, were modeled into a previously determined CesA8 small-angle X-ray scattering molecular envelope to produce a detailed topological model of the CesA8 catalytic domain. The predicted position for the P-CR domain from the molecular docking models places the P-CR connector loop into a hydrophobic pocket of the catalytic core, with the coiled-coil aligned near the entrance of the substrate UDP-glucose into the active site. In this configuration, the P-CR coiled-coil alone is unlikely to regulate substrate access to the active site, but it could interact with other domains of CesA, accessory proteins, or other CesA catalytic domains to control substrate delivery.